A way forward towards a technology‐driven development of industry 4.0 using big data analytics in 5G‐enabled IIoT. (24th October 2021) - Atharvan, Gannu; Koolikkara Madom Krishnamoorthy, Sreelakshmi; Dua, Amit; Gupta, Shashank
Summary: The evolution of Internet of Things (IoT) has led to the development of Industrial Internet of Things (IIoT). IIoT is one the widely applied areas to facilitate people in the manufacturing world. The adoption of IIoT automates sensing, capturing, communicating, and processing in real time. To understand how rapidly IoT and IIoT are growing, this article examines the emergence of 5G‐enabled IIoT, current research trends in IIoT, key milestones achieved in IIoT, and IoT applications specific to 5G‐enabled IIoT. The paper presents the state‐of‐the‐art in networking layered framework of IIoT and comparing relationships of technologies of cloud computing as well as edge computing paradigms. We also explored the type of security attacks and their preventive measures in an IIoT‐driven 5G technology. We have also highlighted the revolution of IIoT‐driven 5G framework which satisfies the demands of IIoT applications. Abstract : In this article, we have described about the 5G technology for the Industrial IoT and how it has revolutionized IIoT by expanding the communication capabilities and let to the development of 5G‐enabled IIoT to cater to the needs and demands of specific IIoT applications. The main security threats and challenges to security in IoT and 5G‐enabled IIoT are identified, and preventive measures for each type of security attacks are suggested.